Reliability Performance Of Epoxy Based Electrically Conductive Adhesive With Varying Multiwalled Carbon Nanotube - Nasaruddin, Muhamad Muaz (2019)
Over the last twenty years, there is a rapid development in microelectronic industries to support sustainable manufacturing globally, which includes the use of more environmental- friendly interconnect materials. Carbon-based ECA is proposed to replace conventional materials such as lead solder alloy (Sn/Pb), lead-free solder alloy (Sn/Ag/Cu) and metal- based ECA. Carbon-based ECA such as MWCNT filled adhesive offer toxicity-free, low processing temperature and oxidation free which can benefit the ECA in many aspects. However, MWCNT is known to constraint the ECA performance in terms of electrical properties. In addition, a polymer-based binder such as epoxy could deteriorate under elevated temperature and humid conditions. Hence, the main objectives of this study are to investigate the effect of filler loading and aspect ratio of multi-walled carbon nanotubes (MWCNTs) on the volume resistivity of ECA, to evaluate the effect of filler loading and aspect ratio of multi-walled carbon nanotubes on the adhesion strength of ECA and to assess the effect of hygrothermal aging on the volume resistivity and adhesion strength of ECA with varying filler loading and aspect ratio. 112.5 (L-MWCNT) and 1750.0 (H-MWCNT)are MWCNT aspect ratios considered in this study. Meanwhile, the range of MWCNT filler loading considered for the ECA is between 3 to 8 wt.%. A four-point probe was employed to evaluate the volume resistivity of ECA using ASTM F390 as a guideline. Meanwhile, a universal testing machine (UTM) was utilized to conduct the single-bonded joint test to evaluate the ECA adhesion strength in accordance with the ASTM D1002. In addition, hygrothermal aging test was performed by using an environmental chamber to assess the influence of severe environmental conditions towards the volume resistivity and the adhesion strength of ECA. Regardless of the range of filler loading, it was found that H- MWCNT filled ECA exhibits superior performance than those of the L-MWCNT in terms of the electrical conductivity and adhesion strength when subjected to hygrothermal aging up to 504 hours. As an example, at 5 wt.%, the H-MWCNT recorded lower volume resistivity than those of the L-MWCNT filled ECA, which could be attributed to its great flexibility which increased the filler tends to be in contact with each other. Consequently, better electron pathway is established within the ECA system, which yields an improved electrical conductivity. Moreover, the H-MWCNT filled ECA is approximately 34% stronger in adhesion strength than those of the L-MWCNT filled ECA, possibly due to an efficient stress distribution with longer tube length of the MWCNT filler. Nonetheless, when subjected to hygrothermal aging, both types of ECA exhibit a similar trend in which the volume resistivity increased, with the H-MWCNT being more resistant, possibly due to greater humidity barrier towards the moisture ingression into the ECA composite system. Overall, it can be concluded that higher aspect ratio of the MWCNT filled ECA exhibit better functional performance with and without the hygrothermal aging conditioning.